Anatomical structure, flavonoid content, and antioxidant activity of Rhodomyrtus tomentosa leaves and fruits on different age and maturity level - evi kuntorini; LAURENTIUS HARTANTO NUGROHO; MARYANI; TRI RINI NURINGTYAS (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Kuntorini EM, Nugroho LH, Maryani, Nuringtyas TR. 2019. Anatomical structure, flavonoid content, and antioxidant activity of Rhodomyrtus tomentosa leaves and fruits on different age and maturity level. Biodiversitas 20: 3619-3625. Karamunting (Rhodomyrtus tomentosa (Aiton.) Hassk.) is a native plant to southeast Asian countries, and is a well-known medicinal plant used to treat colic diarrhea, wounds, heartburn, abscesses, gynecopathy, and as a pain killer. However, the use of R. tomentosa has not been optimized. This research aimed to observe the anatomical structure, the location, and distribution of flavonoid and to find out the antioxidant activity based on the leaves age and the fruit maturity. Anatomical slides preparation of leaves and fruits were made using the paraffin embedding method with safranin staining. The distribution of flavonoid was analyzed by histochemical test and antioxidant activity was done with DPPH (1,1-diphenyl-2-picrylhydrazyl) method. Leaf anatomical structure shows that the leaf bifacial (dorsiventral) consisted of upper epidermis, mesophyll (palisade and sponge), collateral vascular bundle, parenchyma midrib, abaxial epidermis, globular oil cavity, and non-glandular trichome. Transverse section of green fruit consists of exocarp (thin outer layer), mesocarp (thick inner layer, soft and runny) and endocarp (thin false septa) layers. The histochemical test showed that flavonoid was observed in the leaf epidermis, mesophyll, vascular bundles, secretory cavity, parenchyma and in all fruit types exocarp, mesocarp, endocarp. Antioxidant activity showed that the extract of the young leaves (IC50 = 14.67 ppm) was stronger than the old leaves (IC50 = 19.86 ppm). The antioxidant activity of the purple fruits extract (IC50 = 12.98 ppm) was stronger than the red fruits (IC50 = 28.63 ppm) and the green fruits (IC50 = 48.36 ppm) but it was weaker than quercetin (IC50 = 1.29 ppm). The purple fruit had the highest antioxidant activity compared to other extracts. This information will be useful for developing karamunting as a potential resource of natural antioxidants for functional foods and health products.